Recurrent granular myringitis: Medical management revisited - Surbhi; Shaheen Zafar; Rohit Kumar (Asian Journal of Medical Sciences, 2022)
Background: Granular myringitis (GM) is one of the rarer conditions reported in Indian literature. It is defined as a chronic inflammation limited to squamous layer of tympanic membrane. Several names have been given to it such as myringitis granulosa, acute granulomatous myringitis, and chronic myringitis. Aims and Objectives: The objective of our study is to evaluate the results of topical antibiotic with steroids and topical antibiotic alone on disease pathology of GM and its outcome. Materials and Methods: This study was conducted in the department of otorhinolaryngology on 80 patients from the period of September 2020–December 2021 on patients of GM after complete clinical evaluation. This is a prospective study made on two groups of patients. The results were analyzed by visual analog scale. Results: Both the groups after a period of 6 months showed improved results. The outcome with antibiotic with steroid was comparatively faster and superior than antibiotic only ear drops. Conclusion: The result of antibiotic with steroid ear drops is superior to antibiotic only ear drops in the treatment of recurrent GM.